Episodic rhythmicity is generated by a distributed neural network in the developing mammalian spinal cord - Jonathan J. Milla-Cruz; Adam P. Lognon; Michelle A. Tran; Stephanie A. Di Vito; Carlotta Löer; Anchita Shonak; Matthew J. Broadhead; Gareth B. Miles; Simon A. Sharples; Patrick J. Whelan (iScience)
Summary: Spinal circuits generate locomotor rhythms, but the mechanisms behind episodic locomotor behaviors remain unclear. This study investigated dopamine-induced episodic rhythms in isolated neonatal mouse spinal cords to understand these mechanisms. The episodic rhythms were generally synchronous and propagated rostro-caudally, although occasional asynchrony was observed. Electrical stimulation of the L5 dorsal root entrained the episodic rhythms, suggesting afferent control and a distributed network. Even after transection or ventrolateral funiculus (VLF) lesions, episodic activity persisted in isolated thoracic or sacral segments, implying VLF-coupled networks. Rhythmicity was observed in VLF and dorsal root axons and was independent of cholinergic excitation via motoneurons, GABAA receptors, or dorsal inhibitory circuits. These findings suggest a flexibly coupled, distributed spinal interneuron network underlies episodic rhythmicity, providing a foundation for future investigations into how spinal circuits are modulated to produce diverse motor outputs.